2006
DOI: 10.1007/s11150-006-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Move to a Linear Tax System in Germany and Other European Countries

Abstract: A unitary model is then estimated on these collective data and unitary and collective responses to a tax reform are compared. We focus on the introduction of linear taxation in Germany. The exercise is replicated for other European countries and other topical reforms. Distortions due to the use of a unitary model turn out to be important in predicting labour supply adjustments, in the design of tax revenue neutral reforms, and in predicting a reform's welfare implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…It is then possible to use data on singles to complement the “pure,” collective identification. For instance, a series of papers recently published in the Review of Economics of the Household (Bargain et al 2006; Beninger et al 2006; Myck et al 2006; Vermeulen et al 2006) consider a collective model of labor supply with public and private consumption, and assume that the marginal rate of substitution between leisure and private consumption is independent of marital status. Then the model is fully identified.…”
Section: Tests Identification and Estimation Resultsmentioning
confidence: 99%
“…It is then possible to use data on singles to complement the “pure,” collective identification. For instance, a series of papers recently published in the Review of Economics of the Household (Bargain et al 2006; Beninger et al 2006; Myck et al 2006; Vermeulen et al 2006) consider a collective model of labor supply with public and private consumption, and assume that the marginal rate of substitution between leisure and private consumption is independent of marital status. Then the model is fully identified.…”
Section: Tests Identification and Estimation Resultsmentioning
confidence: 99%
“…In such studies, the (hypothetical) introduction of a flat income tax and its impact on the supply of labour is frequently analysed, for example, Decoster et al (2010) studied the introduction of a flat tax in Belgium and found that a flat-tax system could potentially increase labour supply. The introduction of linear taxation in Germany was examined in Beninger et al (2006) and Fuest et al (2008). Beninger et al compared the effects in a computed manner by using a unitary and collective labour supply model.…”
Section: Iza Journal Of European Labor Studiesmentioning
confidence: 99%
“…The method of 'borrowing' preferences from one population group and applying it to another has been used before in the literature, recently in the application of the collective model of labour supply in Beninger et al (2006Beninger et al ( , 2007, Myck et al (2006), Vermeulen et al (2006). In these applications the assumptions were much stronger compared to those we make in this artilce, as in these instances preferences of single individuals (without children) were used for individuals living in couples (with or without children).…”
Section: Assumptions Necessary To Identify the Sharing Parametermentioning
confidence: 99%
“…The relatively straightforward application of the unitary model in a discrete framework -especially following the method proposed by Aaberge et al (1995) and van Soest (1995) -make it by far the more often used. However, recent advances in the development of the collective methodology (e.g Chiappori, 1997;Blundell et al, 2005) and successful applications of the model which combined estimation and calibration, such as Beninger et al (2006), have demonstrated that ignoring the processes that take place within the household leads to misleading conclusions concerning the behaviour of individuals in couples.…”
Section: Introductionmentioning
confidence: 99%